Beyond patriotic discourse in financing the SDGs: investment-linked diaspora revenue bonds model for sub-Saharan Africa. Issue 4 (19th May 2017) - Frimpong Boamah, Emmanuel; Osei, Davina; Yeboah, Thomas
ABSTRACT: Mobilising and sustaining investment flows are two interrelated challenges of development financing. Given the untapped potential of remittances and knowledge flows of sub-Saharan Africa diasporas, an investment-linked diaspora revenue bonds model is proposed to target three issues: generating diaspora investments, which will not be used to service sovereign debts; linking such investments to projects, programmes, and sectors with high economic returns; and developing hybridised institutional frameworks of local and diaspora actors to manage this investment. This model, a hybrid of sovereign and corporate bonds, draws lessons from the Sukuk market and other diaspora bonds to offer an alternative solution to the multi-dimensional nature of development financing challenges confronting SSA countries.